The extent to which companies adhere to disclosure controls in accordance with the requirements of IAS in light of Covid-19 - Hasan, Ibrahim Naeem (Utan Kayu Publishing, 2022)
Therefore, this research was devoted to highlighting the importance of accounting disclosure in the financial statements of commercial banks in accordance with international accounting and financial reporting standards through a proposed model for accounting disclosure in the financial statements of these companies and then applying it to them and helping users of financial statements to make rational decisions as well as evaluating performance. It is concluded that the standard deviation values are confined between (0.70 - 1.023), which are relatively small values, which indicates the homogeneity of the answers to the paragraphs related to the importance of disclosure according to the requirements of financial reporting standards in light of the Corona pandemic, which requires the adoption of international accounting and reporting standards in order to standardize the presentation of those Reports and improving accounting disclosure in the financial reports of commercial banks, which contributes to building bridges of trust and activating The relationship between the management of companies and the beneficiaries of the financial reports and to stay away as much as possible from the multiplicity Presentation and accounting disclosure methods pursued by some companies.